Productive performance of yellow mealworm larvae in different protein and carbohydrate levels in the same energy substrate - G.X. Huang; Y.R. Zhang; T.H. Yu; B.Q. Yuan; D.W. Huang; J.H. Xiao (Animal)
Yellow mealworm (Tenebrio molitor) larvae can efficiently convert waste into high-quality insect protein. However, the specific nutritional requirements of Tenebrio molitor larvae remain largely unclear. Therefore, this study aimed to investigate the optimal substrate composition in terms of protein and carbohydrate content for rearing Tenebrio molitor larvae for food and feed applications. Five isoenergetic and isolipid substrates were formulated, with protein content ranging from 10 to 30%, carbohydrate content ranging from 29.72 to 68.15%, and a protein-to-carbohydrate ratio varying from 1:1 to 1:7. Three replicates of larvae (approximately 10 mm in length, 15 g per replicate, approximately 1 297 larvae per box) were fed each substrate for 8 weeks under controlled conditions in a constant-temperature incubator and subsequently harvested. The results demonstrated that larvae fed on a substrate containing 15% protein (corresponding to 58.34% carbohydrate content) and a protein-to-energy ratio of 10.19 g/MJ achieved the highest final yield, the most efficient food conversion, and the greatest substrate protein conversion efficiency. Additionally, feeding substrates with higher protein content negatively impacted larval growth. In summary, this study concluded that to achieve high yields while ensuring optimal utilisation of substrate resources and minimising feeding costs, it is recommended to use a substrate with 15% protein content, a protein-to-carbohydrate ratio of 1:5, and a protein−to−energy ratio of 6.82 g/MJ.